Geo-accumulation and Ecological Risk Assessment of Heavy Metals From Roadside Dust Around Forces Avenue, Old GRA, Port Harcourt, Nigeria (Global Journal of Science Frontier Research, 2018)
Samples from roadside dust collected from different stations in Forces Avenue, Old GRA, Port Harcourt, Rivers State, Nigeria were digested (mineralized) and subsequently analyzed for heavy metals concentration. The result of the investigation showed that Iron (Fe) was the most abundant metal detected in the roadside. The highest value of Fe was obtained in station 2, which was 81.40±8.12 mg/Kg. The order of concentration of the metals was iron (Fe) >zinc (Zn) > nickel (Ni) > copper (Cu) > lead (Pb) >cadmium (Cd) > chromium (Cr). The mean concentrations of the heavy metals from the various stations was: Fe (71.08±5.38), Zn (47.34±6.05), Ni (25.27±0.99), Cu (18.08±0.93), Pb (0.54±0.05), Cd (0.36±0.03) and Cr (0.18±0.05) mg/Kg. Contamination factor analysis showed that the Forces Avenue area is within contamination category, but not yet polluted with heavy metals. Geo-accumulation index and ecological risk assessment interpretations showed that the concentration of heavy metals in the environment arose from natural factors and pose no ecological risk to the environment. However, adequate care and control should be put in place to put the environment under check to avert possible rise in the concentrations of the metals especially Zn, Ni and Cu.
Keywords: heavy metals; roadside dust; geoaccumulation; ecological risk; contamination factor; assessment